2020
DOI: 10.1017/s0033291720003086
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity, decision-making and risk-taking behaviour in bipolar disorder: a systematic review and meta-analysis

Abstract: Despite the robust body of work on cognitive aspects of bipolar disorder (BD), a clear profile of associated impairments in impulsivity, decision-making and risk-taking from studies that use behavioural measures has yet to be established. A systematic review, across four electronic databases (PsycINFO, MEDLINE/PubMed, ScienceDirect and Scopus), of literature published between January 1999 and December 2018 was carried out in accordance with the PRISMA statement. The protocol was registered on PROSPERO (CRD4201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 54 publications
6
42
3
Order By: Relevance
“…Furthermore, qualitative research is required to identify ways to tailor content to the specific needs, interests, and vulnerabilities among people with BD. For example, impulsivity and risk taking is characteristic of hypomanic/manic states in BD [ 67 ]; as such, modules may need to provide education and strategies addressing how evaluation of privacy/financial risks of health apps can be impacted by BD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, qualitative research is required to identify ways to tailor content to the specific needs, interests, and vulnerabilities among people with BD. For example, impulsivity and risk taking is characteristic of hypomanic/manic states in BD [ 67 ]; as such, modules may need to provide education and strategies addressing how evaluation of privacy/financial risks of health apps can be impacted by BD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that patients made significantly fewer average balloon pumps in unexploded trials and had lower explosion rate than controls, indicating their increased tendency for risk aversion. This is, however, contrary to a recent meta-analysis which found no significant impairment in risk-taking behavior in bipolar disorder, in terms of the pooled estimate for the entire sample or individual behavioral tasks (2). Some previous studies (7,9,10) and stratified analysis of the meta-analytic review (2) further revealed elevated risk-taking behavior in bipolar disorder patients, particularly those with bipolar I disorder.…”
Section: Discussioncontrasting
confidence: 69%
“…Behavioral findings using this approach have been inconsistent in BD and difficult to compare across studies (Bauer et al, 2017;Hidiroǧlu et al, 2013;Holmes et al, 2009;Linke et al, 2013;Ramírez-Martín et al, 2020;Reddy et al, 2014;Scholz et al, 2016). One reason is the heterogeneity of mood state between investigations (Ramírez-Martín et al, 2020).…”
Section: Inconsistent Behavioral Findings Due To Sample Heterogeneitymentioning
confidence: 99%
“…Behavioral findings using this approach have been inconsistent in BD and difficult to compare across studies (Bauer et al, 2017;Hidiroǧlu et al, 2013;Holmes et al, 2009;Linke et al, 2013;Ramírez-Martín et al, 2020;Reddy et al, 2014;Scholz et al, 2016). One reason is the heterogeneity of mood state between investigations (Ramírez-Martín et al, 2020). Some have studied purely euthymic samples (Hidiroǧlu et al, 2013;Linke et al, 2013;Scholz et al, 2016), while others have studied samples containing a mixture of hypo/manic, euthymic, and depressed participants (Bauer et al, 2017;Holmes et al, 2009;Reddy et al, 2014).…”
Section: Inconsistent Behavioral Findings Due To Sample Heterogeneitymentioning
confidence: 99%